Impact of Co2 laser cutting parameters on the quality of cut on PMMA sheet - Heng, Yee Wien (2010)
The quality of laser cut is of the utmost importance in laser cutting process. All cutting parameters might have significant influence on the resulting quality of work. In general, cutting parameters are adjusted and tuned to provide the quality of cut desired. But this consumes exhaustive amounts of time and effort. Therefore, it is important to investigate the impact of cutting parameters on quality of cut. The aim of this study is to relate the CO2 laser cutting parameters namely laser power, cutting speed and tip distance to the quality of cut of PMMA sheet. The quality parameters considered include surface roughness, kerf width and heat affected zone. The effects of each cutting parameters on quality of cut was establish and the interactions between the cutting parameters were investigated.Design of experiment was used by implementing Box-Behnken design to identify the main effects and interactions of the parameters. Perthometer S2 and microscope MarVision MM320 are carried out to examine the surface roughness, kerf width and heat affected zone. The yields of responses are then analyzed by using STATISTICA software. The statistical analysis reveals that the surface roughness and kerf width are significantly affected by tip distance followed by cutting speed. Laser powers do affect the surface roughness and kerf width but its effects are negligible when compared to cutting speed and tip distance. It is also found that all three cutting parameters have significant effects on the variation of heat affected zone. A significant interaction exists between cutting speed and tip distance as shown in statistical analysis.